A Field Guide for Monitoring Riverine Macroplastic Entrapment in Water Hyacinths - Schreyers, Louise; van Emmerik, Tim; Nguyen, Thanh Luan; Phung, Ngoc-Anh; Kieu-Le, Thuy-Chung; Castrop, Evelien; Bui, Thanh-Khiet L.; Strady, Emilie; Kosten, Sarian; Biermann, Lauren; van den Berg, Sanne J.P.; van der Ploeg, Martine (Frontiers in Environmental Science, 2021)
River plastic pollution is an environmental challenge of growing concern. However, there are still many unknowns related to the principal drivers of river plastic transport. Floating aquatic vegetation, such as water hyacinths, have been found to aggregate and carry large amounts of plastic debris in tropical river systems. Monitoring the entrapment of plastics in hyacinths is therefore crucial to answer the relevant scientific and societal questions. Long-term monitoring efforts are yet to be designed and implemented at large scale and various field measuring techniques can be applied. Here, we present a field guide on available methods that can be upscaled in space and time, to characterize macroplastic entrapment within floating vegetation. Five measurement techniques commonly used in plastic and vegetation monitoring were applied to the Saigon river, Vietnam. These included physical sampling, Unmanned Aerial Vehicle imagery, bridge imagery, visual counting, and satellite imagery. We compare these techniques based on their suitability to derive metrics of interest, their relevancy at different spatiotemporal scales and their benefits and drawbacks. This field guide can be used by practitioners and researchers to design future monitoring campaigns and to assess the suitability of each method to investigate specific aspects of macroplastic and floating vegetation interactions.